Akibat Hukum Pembubuhan Cap Ibu Jari Sebagai Pengganti Tanda Tangan Dalam Pembuatan Akta Notaris - Vitasari, Diana Agatha; Musyafah, Aisyah Ayu (Fakultas Syariah INSURI Ponorogo, 2023)
A notarial deed must be signed by the parties involved. In some cases, the parties involved cannot put their signatures. The purpose of this study was to find out whether thumbprints can replace signatures in making notarial deeds and their legal consequences. This study uses normative legal research with secondary data and library research. The results of this study according to Article 1874 of the Civil Code and Article 44 paragraphs (1) and (2) of the UUJN regulates the affixing of a thumbprint as a substitute for a signature in making notarial deeds to people who are sick or disabled to read and write. These articles state that affixing a thumbprint as a substitute for a signature can be done on condition that the affixing must be done before an authorized official (Notary) and the Notary is required to include information or reasons regarding the person not being able to sign. The legal consequences of a deed not being signed are replaced by using a thumbprint, which is still valid and legally binding as an authentic deed as long as the provisions contained in Article 1874 of the Civil Code and Article 44 paragraphs (1) and (2) UUJN are fulfilled.